2023
DOI: 10.1186/s13063-023-07641-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of video laryngoscope, video stylet, and flexible videoscope for transoral endotracheal intubation in patients with difficult airways: a randomized, parallel-group study

Tao Zhang,
Kai-Yuan Zhao,
Ping Zhang
et al.

Abstract: Background The 2022 ASA guidelines recommend the video laryngoscope, video stylet, and flexible videoscope as airway management tools. This study aims to compare the efficacy of three airway devices in intubating patients with difficult airways. Methods A total of 177 patients were selected and randomized into the following three groups: the video laryngoscope group (Group VL, n = 59), video stylet group (Group VS, n = 59), and flexible videoscope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…However, video laryngoscopy may not be appropriate for patients with limited mouth opening capacity or cervical spinal injuries. A recent study comparing the efficacy of flexible videoscopes, video laryngoscopes, and video stylets for orotracheal intubation under general anesthesia in patients with difficult airways found that video stylets and flexible videoscopes yielded higher rates of successful first-attempt intubations and better glottic exposure than video laryngoscopes [ 8 ]. Additionally, the use of video stylets for endotracheal intubation resulted in a significant reduction in intubation time compared with both the video laryngoscope and flexible videoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, video laryngoscopy may not be appropriate for patients with limited mouth opening capacity or cervical spinal injuries. A recent study comparing the efficacy of flexible videoscopes, video laryngoscopes, and video stylets for orotracheal intubation under general anesthesia in patients with difficult airways found that video stylets and flexible videoscopes yielded higher rates of successful first-attempt intubations and better glottic exposure than video laryngoscopes [ 8 ]. Additionally, the use of video stylets for endotracheal intubation resulted in a significant reduction in intubation time compared with both the video laryngoscope and flexible videoscope.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Disposcope endoscope does have some limitations, such as the lack of a working channel for suctioning secretions, which may compromise visualization if considerable secretions are present. This limitation can be overcome by positioning the lens at the Murphy’s orifice of the tracheal tube without moving the lens over the tip and by improving the operational skill [ 8 ]. Although Disposcope endoscopes have recently been used for awake nasotracheal intubation [ 10 ], to date, reports on the use of Disposcope endoscope for awake orotracheal intubation are limited.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated, in this article, that styletubation serves well for such goal of tracheal intubation in this particular clinical scenario (Table 2). With the increasing attention at the styletubation technique in various clinical scenarios [67,96,[106][107][108], we believe the potential clinical role of styletubation will eventually supersede that of laryngoscopy in the near future. In conclusion, in obese patients undergoing bariatric surgery, the role of routine application of styletubation is promising and worthy to test.…”
Section: Discussionmentioning
confidence: 99%